University Admissions: Practices and Procedures Worldwide - Helms, Robin (International Higher Education, 2009)
In a study examining tertiary admissions criteria at public universities in 15 countries, several distinctive models emerge. Admissions may be determined by government agencies, individual institutions, or independent organizations and are based upon secondary-school leaving examinations, entrance examinations, standardized aptitude tests, secondard school grades, or a combination of factors.